1995
DOI: 10.1083/jcb.128.5.949
|View full text |Cite
|
Sign up to set email alerts
|

Association of p120, a tyrosine kinase substrate, with E-cadherin/catenin complexes.

Abstract: Abstract. p120 was originally identified as a substrate of pp6@ ~ and several receptor tyrosine kinases, but its function is not known. Recent studies revealed that this protein shows homology to a group of proteins, ~-catenln/Armadillo and plakoglobin (,y-catenin), which are associated with the cell adhesion molecules cadherins. In this study, we examined whether p120 is associated with E-cadherin using the human carcinoma cell line HT29, as well as other cell lines, which express both of these proteins. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
183
3
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(195 citation statements)
references
References 53 publications
7
183
3
2
Order By: Relevance
“…p120 can regulate Ecadherin, a cell-cell adhesion molecule that functions as a component of the adherens junction of epithelial tissues, and turnover of E-cadherin is regulated by binding of p120 to the cadherin juxtamembrane domain (Reynolds et al, 1989;Reynolds et al, 1992Reynolds et al, , 1994Shibamoto et al, 1995;Staddon et al, 1995;Anastasiadis et al, 2000;Thoreson et al, 2000;Anastasiadis and Reynolds, 2001;Ireton et al, 2002;Davis et al, 2003;Reynolds and Carnahan, 2004). Studies have demonstrated that loss of E-cadherin or overexpression of p120 results in mislocalization of p120 to the cytoplasm (Reynolds and Carnahan, 2004), where it induces a range of morpho- Figure 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p120 can regulate Ecadherin, a cell-cell adhesion molecule that functions as a component of the adherens junction of epithelial tissues, and turnover of E-cadherin is regulated by binding of p120 to the cadherin juxtamembrane domain (Reynolds et al, 1989;Reynolds et al, 1992Reynolds et al, , 1994Shibamoto et al, 1995;Staddon et al, 1995;Anastasiadis et al, 2000;Thoreson et al, 2000;Anastasiadis and Reynolds, 2001;Ireton et al, 2002;Davis et al, 2003;Reynolds and Carnahan, 2004). Studies have demonstrated that loss of E-cadherin or overexpression of p120 results in mislocalization of p120 to the cytoplasm (Reynolds and Carnahan, 2004), where it induces a range of morpho- Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…A host molecule that has been implicated in regulation of MMP-7 expression is p120-catenin (p120). p120 was originally identified as a substrate for Src-and receptor-tyrosine kinases (Reynolds et al, 1989(Reynolds et al, , 1992Reynolds and Carnahan, 2004) and is a member of the catenin (ctn) family, an Armadillo domain protein subfamily whose members interact with the cadherin cytoplasmic tail and modulate cadherin function (Reynolds et al, 1994;Shibamoto et al, 1995;Staddon et al, 1995;Reynolds and Carnahan, 2004). Aberrant redistribution of p120 has been observed in several epithelial malignancies, including gastric cancer (Jawhari et al, 1999;Karatzas et al, 1999;Karayiannakis et al, 1999;Thoreson and Reynolds, 2002;Mayerle et al, 2003).…”
mentioning
confidence: 99%
“…At adherens junction, cadherins interact with each other at the extracellular surface and serve as adhesion molecules (for reviews, see Geiger and Ginsberg, 1991;Tsukita et al, 1992;Takeichi, 1995). Cadherins indirectly interact at the cytoplasmic region with the actin cytoskeleton through many peripheral membrane proteins, including a-, b-, and g-catenins, p120, a-actinin, vinculin, neurabin, and afadin (Vestweber and Kemler, 1984;Peyrieras et al, 1985;Ozawa et al, 1989;Shibamoto et al, 1995;Nakanishi et al, 1997;Mandai et al, 1997). Tight junction also plays an important role in the formation of cell polarity and barrier (for reviews, see Schneeberger and Lynch, 1992;Gumbiner, 1993;Anderson and Van Itallie, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a reduction in E-cadherin often results in b-catenin degradation (Liu et al, 2002). Another protein associated with E-cadherin, p120 (Thoreson et al, 2000), is phosphorylated on both tyrosine and serine residues in response to a variety of growth factors such as epidermal growth factor (EGF), platelet-derived growth factor (PDGF), and colony stimulating factor (CSF)-1, suggesting involvement in active signalling (Downing and Reynolds, 1991;Shibamoto et al, 1995). Thus, cell -cell adhesion serves not only a structural role but dictates cellular behaviour.…”
mentioning
confidence: 99%